(untitled) (TAJ: Journal of Teachers Association, 2021)
Micronutrient deficiencies, especially those related to iodine and iron, are linked to different cognitive impairments, as well as to potential long-term behavioral changes. Among the cognitive impairments caused by iron deficiency, those referring to attention span, intelligence, and sensory perception functions are mainly cited, as well as those associated with emotions and behavior, often directly related to the presence of iron deficiency anemia. In addition, iron deficiency without anemia may cause cognitive disturbances. At present, the prevalence of iron deficiency and iron deficiency anemia is 2%–6% among European children. Given the importance of iron deficiency relative to proper cognitive development and the alterations that can persist through adulthood as a result of this deficiency, the objective of this study was to review the current state of knowledge about this health problem. The relevance of iron deficiency and iron-deficiency anemia, the distinction between the cognitive consequences of iron deficiency and those affecting specifically cognitive development, and the debate about the utility of iron supplements are the most relevant and controversial topics. Despite there being methodological differences among studies, there is some evidence that iron supplementation improves cognitive functions. Nevertheless, this must be confirmed through adequate follow-up studies among different groups. TAJ 2021; 34: No-1: 115-122